2021
DOI: 10.1002/app.50693
|View full text |Cite
|
Sign up to set email alerts
|

Cover Image, Volume 138, Issue 23

Abstract: This cover designed by Jingmiao Zhang and colleagues shows four kinds of agricultural waste particles such as (XS: OS/oilseed rape straw, RS/rice straw, WS/wheat straw and CS/corn stover). The image shows how they were used to reinforce agricultural waste liquefied polyol‐based polyurethane foam (XSPU). RS particles show great promoting ability and OS particles reveal complex influence, while WS and CS particles display mild effect on the foaming process. With 1% of OS, 6% of RS, 3% of WS or 1% of CS incorpora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(29 citation statements)
references
References 0 publications
0
29
0
Order By: Relevance
“…It indicated that CSPU showed the lowest thermal stability, while WSPU displayed the highest thermal stability. Because P‐CS had a lower hydroxyl number than the other three bio‐polyols 33 and less pMDI was needed when preparing CSPU at 1.5:1 of NCO/OH ratio. Therefore, the CSPU contained fewer urethane segments and its polymer chain appeared to be simpler than other foams and displayed weaker thermal stability.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It indicated that CSPU showed the lowest thermal stability, while WSPU displayed the highest thermal stability. Because P‐CS had a lower hydroxyl number than the other three bio‐polyols 33 and less pMDI was needed when preparing CSPU at 1.5:1 of NCO/OH ratio. Therefore, the CSPU contained fewer urethane segments and its polymer chain appeared to be simpler than other foams and displayed weaker thermal stability.…”
Section: Resultsmentioning
confidence: 99%
“…The OS was obtained from Tohoku Agricultural Research Center (Iwate, Japan), while RS, WS, and CS were obtained from The University of Tokyo experimental farm. The XS was liquefied at 150°C for 40 min with 62.7 wt% polyethylene glycol 400 (PEG, Wako, AR) and 20.9 wt% ethylene glycol (EG, Wako, AR) as solvents, and 3 wt% sulfuric acid (Wako, AR) as a catalyst 33 . These P‐XSs were neutralized by 48% NaOH aqueous solution before subsequent application.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations